Conductive Screen Printing Inks by Gelation of Graphene Dispersions. (15th December 2015) - Arapov, Kirill; Rubingh, Eric; Abbel, Robert; Laven, Jozua; de With, Gijsbertus; Friedrich, Heiner
Abstract : This paper describes the gelation of highly concentrated graphene/polymer dispersions triggered by mild heating. The gel formation is only dependent on the concentration of graphene with 3.25 mg mL −1 as the minimum value for graphene network formation. The graphene gel is then utilized for the preparation of colloidally stable and highly concentrated (52 mg mL −1 ) graphene pastes that demonstrate excellent performance in screen printing down to lines of 40 μm in width. Printed patterns dried at 100 °C for only 5 min exhibit sheet resistances of 30 Ω  −1 at 25 μm thickness, thus, removing the need for long‐time high temperature annealing, doping, or other treatments. Such a low drying temperature, high printing definition, and compatibility with industrially relevant plastic and paper substrates brings high‐volume roll‐to‐roll application in printed flexible electronics within reach. Abstract : Graphene screen printing using a paste obtained by gelation of highly concentrated graphene dispersions is demonstrated. The graphene paste shows a high printing definition, enabling printing of 40 μm wide lines on PET foil and paper substrates. A sheet resistance of 30 Ω  −1 at 25 μm is achieved after drying at 100 °C for 5 min, which brings high‐speed, high‐volume applications within reach.